The Influence of Murabaha Financing Funds on the Business Development of Rizky Prima Sejahtera KSPPS Members - Muhamad Indra Davfa; Retnosari Retnosari (Transpublika Publisher, 2024)
One of the service products offered by KSPPS Rizky Prima Sejahtera is a sale- purchase financing contract based on murabahah. Murabahah is a financing contract for the sale and purchase of goods at the original price (acquisition price) with additional profit (margin) agreed by both parties (seller and buyer). The goal of this research is to examine how the murabahah financing provided by Rizky Prima Sejahtera KSPPS impacts the growth of the businesses belonging to its members. By cooperating with KSPPS through murabahah financing, people who lack capital can develop their micro businesses. The authors utilized qualitative research methods to gather information, including conducting interviews, reviewing documents, studying literature, and employing descriptive analysis techniques in their data analysis. Also, based on the results of the study, it shows that the murabahah financing fund has a positive effect on the business development of MSME members of KSPPS Rizky Prima Sejahtera.